ROLE OF POTENTIAL AND COMPETENCY ASSESSMENTS IN PREDICTING PERFORMANCE APPRAISAL OUTCOMES FOR ECHELON III CIVIL SERVANTS IN WEST NUSA TENGGARA - Rivalikal Payanta, Lalu (ShariaBiz International Journal of Economics & Business, 2025)
This study investigates the impact of potential and competency assessments on performance appraisal outcomes for Echelon III administrators in West Nusa Tenggara Province. Using a quantitative approach with data from 60 civil servants, the research highlights the critical role of competency assessments in predicting performance. Competency scores, covering managerial, interpersonal, and technical skills, accounted for 42% of the variance in performance outcomes, while potential scores, including leadership and intellectual capacity, contributed 28%. The combined model explained 62% of the variance, confirming their complementary nature. Competency, particularly strategic analysis, decision-making, and communication, predominantly shapes performance, supported by potential. These assessments support evidence-based HR practices, such as recruitment, promotion, and training, aligning with Indonesia’s bureaucratic reform for transparent, merit-based HR policies. The study enriches talent management literature, offering practical insights for enhancing HR practices in the public sector.